Structural analysis of a replication protein encoded by a plasmid isolated from a multiple sclerosis patient. Issue 5 (7th May 2019) - Kilic, Turgay; Popov, Alexander N.; Burk-Körner, Amelie; Koromyslova, Anna; zur Hausen, Harald; Bund, Timo; Hansman, Grant S.
Abstract : The crystal structure of the WH1 domain of the eukaryotic replication initiator protein (Rep) MSBI1.176 in the dimeric form has been determined to 1.53 Å resolution and shows a number of structural similarities to and differences from other known prokaryotic Reps. Abstract : Bovine meat and milk factors (BMMFs) are circular, single‐stranded episomal DNAs that have been detected in bovine meat and milk products. BMMFs are thought to have roles in human malignant and degenerative diseases. BMMFs encode a replication initiator protein (Rep) that is actively transcribed and translated in human cells. In this study, a Rep WH1 domain encoded on a BMMF (MSBI1.176) isolated from a multiple sclerosis human brain sample was determined to 1.53 Å resolution using X‐ray crystallography. The overall structure of the MSBI1.176 WH1 domain was remarkably similar to other Rep structures, despite having a low (28%) amino‐acid sequence identity. The MSBI1.176 WH1 domain contained elements common to other Reps, including five α‐helices, five β‐strands and a hydrophobic pocket. These new findings suggest that the MSBI1.176 Rep might have comparable roles and functions to other known Reps of different origins.